Prion disease: Review of the literature. - Hernández, Jonattan (2022)
Prion disease are entities of unknown genetic origin that cause in human beings a number of neurological manifestations that lead patients to states of immobility and severe deterioration, with a very poor prognosis and uncertain cure rates. It is difficult to find in the literature important findings to determine the clinical diagnosis and pharmacological methodology to counteract the deterioration of patients suffering from this condition. Therefore, a systematic search was carried out in the PubMed database. Research from 1990 to 2020 that addressed the diagnostic criteria of Creutzfeldt-Jackobs disease in adults, its clinical manifestations, diagnosis and management, recommendations and management guidelines were included to demonstrate the situation of patients who present this type of alterations and deterioration neurological diagnosis of difficult diagnosis, to determine clinical criteria that can give a clinical orientation for the diagnosis of these entities.